International road freight haulage - Kozhushko, A. P. (My University, 2022)
The educational discipline "International road freight haulage" belongs to the selective disciplines of the professional training of a master's student. It is based on the organization of modern automobile transportation.
Keywords: methodological instructive; practical work; cargo transport volumes; specialized rolling stock; vehicle traffic routes; prefabricated routes